Dietary diversity and resource continuity improve fitness and alter flight in a native coccinellid predator, Hippodamia convergens (Coleoptera: Coccinellidae) - Stowe, Hannah (Kansas State University, 2021)
Conservation biological control methods seek to support healthy communities of beneficial predators that can provide predation and pest control services in the agroecosystem. Manipulation of resource availability through land management practices can provide critical support to the survival and ecosystem services of beneficial insect predators. Thus, identifying necessary resource types and ideal arrangement and timing of these resources can improve the efficacy of this land management and improve predation services. Hippodamia convergens Guerin-Meneville is an important generalist insect predator that provides predation services in economically important agricultural systems, especially upon aphids. This species exploits both prey and plant-derived resource and moves among crops throughout the growing season in response to, and in anticipation of, pest populations. Dispersal flight is necessary to discover widely distributed and ephemeral resources, but movement can be metabolically costly and reduce energetic capital for later reproduction and movement expenditure. Discontinuity of resources resulting from spatially and temporally scattered patches influences H. convergens beetles by increasing the need for dispersal. This thesis explored the effects of diet composition and resource continuity on H. convergens development, reproduction and flight capacity, while simultaneously investigating life history tradeoffs between reproduction and dispersal by flight. The effects of diet composition on development, reproductive performance and flight were explored by varying feeding conditions. A monotypic, prey-only diet yielded faster development, and larger adults, but delayed oviposition and reduced fecundity relative to a diet comprised of diverse prey and plant resources. Plant resource availability in the diet was found to hasten oviposition, increasing the number of oviposition days and overall fecundity. Larger adults resulting from greater resource access as larvae delayed oviposition longer and laid fewer clutches, though fecundity was not affected. Potential reproductive effects of diverse resource access include increased population growth, either due to speeding oviposition start times, or through directly increasing egg numbers. Results of flight assays with plant resource diets showed marginal interactions with adult body size, but neither diet composition nor adult size had significant effects on flight distance. Post-reproductive flights were significantly reduced relative to pre-reproductive flights in the same treatment. Thus even though diet treatments were not shown to directly influence flight capacity under our short observation periods, we did see apparent costs of reproduction on later flight. Resource access continuity effects were examined by varying periods of food access and food amount and measuring reproduction and movement capacity in adult beetles. Discontinuous availability of diet components was shown to delay onset of oviposition, reduce individual reproductive days and fecundity, though flight performance was only influenced indirectly through reproductive effects. Thus continuity of resource access can improve biological control services through improvements to population growth rates through faster oviposition and greater egg production. Taken together, these results illustrate important potential benefits of increased plant and insect diversity, along with increased resource continuity to the success and sustainability of biological control programs in the agroecosystem. The results of these studies increase our understanding of the nutritional needs of these important predators and could help to shape future land management strategies to improve biological control. Future work should examine the specifics of flight behavior in conjunction with metabolic activity and examine responses to other prey species and supplemental resources for potential effects on H. convergens fitness and life history.
Keywords: Biological control; Agricultural ecology; Energetic trade-offs; Insect flight; Omnivory